Blackberry and Dewberry: Biology and Control - Jason A. Ferrell; Brent A. Sellers (EDIS)
There are numerous Rubus (blackberry and dewberry) species in the Southeastern U.S., many of which are found in Florida. Blackberry is commonly found in fence rows, ditch banks, and pastures and can be overlooked for extended periods of time. However, lack of management can give rise to thickets that are difficult to control. This document is SS-AGR-240, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 2005.